CDX2, a highly sensitive and specific marker of adenocarcinomas of intestinal origin - An immunohistochemical survey of 476 primary and metastatic carcinomas - Werling, R. W.; Yaziji, H.; Bacchi, C. E.; Gown, A. M. (Lippincott Williams & Wilkins, 2003)
CDX2 is a recently cloned homeobox gene that encodes an intestine-specific transcription factor, expressed in the nuclei of epithelial cells throughout the intestine, from duodenum to rectum. While expression of CDX2 protein in primary and metastatic colorectal carcinomas has been previously documented, neither the sensitivity nor the specificity of CDX2 expression, as determined by immunohistochemistry, for colorectal adenocarcinoma has been determined. We performed an immunohistochemical survey of 476 tumors with a monoclonal antibody, CDX2-88, including 89 tumors from the colon and duodenum and 95 tumors from other gastrointestinal sites, including the esophagus, stomach, pancreatobiliary system, gastrointestinal carcinoids, and liver. CDX2 was expressed uniformly (that is, in 76-100% of tumor cells) in all but one of the evaluated colorectal and duodenal tumors. High-level expression of CDX2 was also found, however, in mucinous ovarian carcinomas and adenocarcinomas primary to the urinary bladder of which 64% and 100% were positive, respectively. Gastric, gastroesophageal, and pancreatic adenocarcinomas and cholangiocarcinomas all showed similar, heterogeneous patterns of CDX2 expression. Most tumors in each group showed CDX2 expression by a minority of cells, whereas a substantial minority of cases in each group was completely negative and a smaller minority was uniformly positive. Gastrointestinal carcinoids gave similarly varied results, but the majority (58%) was negative. Hepatocellular carcinomas showed no expression of CDX2. Only very rare examples of carcinomas of the genitourinary and gynecologic tracts, breast, lung, and head and neck showed significant levels of CDX2 expression. In this study of primary and metastatic epithelial tumors, uniform CDX2 expression is demonstrated to be an exquisitely sensitive and highly, but incompletely, specific marker of intestinal adenocarcinomas. Compared with villin, a previously described marker of GI adenocarcinomas, CDX2 demonstrated superior sensitivity and comparable specificity. CDX2 expression can be seen, however, in selected non-GI adenocarcinomas such as mucinous ovarian carcinomas and adenocarcinomas of the urinary bladder.
Keywords: colonic adenocarcinoma; immunohistochemistry; carcinomas of unknown primary; nuclear transcription factor